Impact of unilateral diaphragm elevation on postoperative outcomes in bilateral lung transplantation – a retrospective single‐center study. (23rd January 2021) - Draeger, Helge; Salman, Jawad; Aburahma, Khalil; Becker, Lena S.; Siemeni, Thierry; Boethig, Dietmar; Sommer, Wiebke; Avsar, Murat; Bobylev, Dmitry; Schwerk, Nicolaus; Müller, Carsten; Greer, Mark; et al.
Summary: This study evaluated the impact of unilateral diaphragm elevation following bilateral lung transplantation on postoperative course. Patient data for all lung transplantations performed at our institution between 01/2010 and 12/2019 were reviewed. Presence of right or left diaphragm elevation was retrospectively evaluated using serial chest X‐rays performed while patients were standing and breathing spontaneously. Right elevation was defined by a > 40 mm difference between right and left diaphragmatic height. Left elevation was present if the left diaphragm was at the same height or higher than the right diaphragm. In total, 1093/1213 (90%) lung transplant recipients were included. Of these, 255 (23%) patients exhibited radiologic evidence of diaphragm elevation (right, 55%; left 45%; permanent, 62%). Postoperative course did not differ between groups. Forced expiratory volume in 1 second, forced vital capacity and total lung capacity were lower at 1‐year follow‐up in patients with permanent than in patients with transient or absent diaphragmatic elevation ( P = 0.038, P < 0.001, P = 0.002, respectively). Graft survival did not differ between these groups ( P = 0.597). Radiologic evidence of diaphragm elevation was found in 23% of our lung transplant recipients. While lung function tests were worse in patients with permanent elevation, diaphragm elevation did not have any relevant impact on outcomes.